Acupressure Therapy as Alternative Treatment on Cancer-Related Fatigue in Cancer Patients - Werdani, Yesiana Dwi Wahyu (STRADA : Jurnal Ilmiah Kesehatan, 2019)
Cancer affects the neurophysiological changes in skeletal muscle progressively and leading to cancer-related fatigue (CRF). Acupressure therapy can stimulate local microcirculation improvement and increasing physical performance. The purpose was determine the influence of acupressure therapy on CRF in cancer patients. The design used pre-experiment one group pre-test post-test design. Samples were 30 cancer patients living at the Indonesian Cancer Foundation East Java Branch taken by purposive technique based on inclusion criteria. The instrument was the Brief Fatigue Inventory. Acupressure therapy is given to acupoint C6, GB20, P6, Li4, Li11, Sp 6, St 36, 2 times per week for 4 weeks. Statistics was verified with Wilcoxon Sign Rank Test p < 0.05. Result showed the effect of acupressure therapy on CRF p = 0.000. Acupressure therapy can activate acupoint on the meridians, stimulating myelin nerves in the muscles and impulses into the central nervous system and can facilitate the reduction fatigue.